2022
DOI: 10.1021/acsbiomedchemau.2c00020
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Demonstration of Human Lipoyl Synthase Catalytic Activity in the Presence of NFU1

Abstract: Lipoyl synthase (LS) catalyzes the last step in the biosynthesis of the lipoyl cofactor, which is the attachment of sulfur atoms at C6 and C8 of an n-octanoyllysyl side chain of a lipoyl carrier protein (LCP). The protein is a member of the radical S-adenosylmethionine (SAM) superfamily of enzymes, which use SAM as a precursor to a 5′-deoxyadenosyl 5′-radical (5′-dA·). The role of the 5′-dA· in the LS reaction is to abstract hydrogen atoms from C6 and C8 of the octanoyl moiety of the substrate to initiate subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 96 publications
(193 reference statements)
0
14
0
Order By: Relevance
“…This is not due to changes in total protein levels of the lipoylated proteins (as shown for DLAT). Cellular protein lipoylation is regulated by the Fe-S cluster enzyme LIAS (25,26) that uses the sulfurs from its auxiliary Fe-S cluster to facilitate the double sulfur insertion to the sixth and eighth carbons of the octanoyl precursor of lipoic acid (18). This dependency of LIAS on Fe-S clusters for function has been shown in genetic models where perturbations to Fe-S cluster biosynthesis results in reduced levels of LIAS and consequently reduced levels of protein lipoylation (27,28).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is not due to changes in total protein levels of the lipoylated proteins (as shown for DLAT). Cellular protein lipoylation is regulated by the Fe-S cluster enzyme LIAS (25,26) that uses the sulfurs from its auxiliary Fe-S cluster to facilitate the double sulfur insertion to the sixth and eighth carbons of the octanoyl precursor of lipoic acid (18). This dependency of LIAS on Fe-S clusters for function has been shown in genetic models where perturbations to Fe-S cluster biosynthesis results in reduced levels of LIAS and consequently reduced levels of protein lipoylation (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…During purification, the SUMO tag was cleaved from the fusion protein affording pure LIAS with a Gly-His appendage at the N-terminus. Both proteins were overexpressed, purified and their respective iron-sulfur clusters reconstituted following procedures as previously published for LIAS with no further modifications (18).…”
Section: Complementation Assay-mentioning
confidence: 99%
See 1 more Smart Citation
“…An Article in this virtual issue from the Booker laboratory describes the characterization of the human form of LipA, called LIAS, as well as the human NfuA analogue, NFU1. This Article reports that NFU1 binds tightly to LIAS and, like NfuA’s effect on LipA, can regenerate the auxiliary cluster of LIAS, allowing the protein to conduct multiple turnovers . A second Article contributed by the Booker laboratory describes studies on a completely new system for generating the lipoyl cofactor that is found predominantly in archaea.…”
Section: Contributions To the Radical Sam Virtual Issue In Acs Bio An...mentioning
confidence: 99%
“…This Article reports that NFU1 binds tightly to LIAS and, like NfuA’s effect on LipA, can regenerate the auxiliary cluster of LIAS, allowing the protein to conduct multiple turnovers. 100 A second Article contributed by the Booker laboratory describes studies on a completely new system for generating the lipoyl cofactor that is found predominantly in archaea. Unlike the canonical system (i.e., LipA and LIAS), which requires only a protein composed of a single polypeptide, this new system requires two proteins to insert both sulfurs.…”
Section: Contributions To the Radical Sam Virtual Issue In ...mentioning
confidence: 99%